Louie & bloop and the swapped shopping - Bostock, Mike (Egmont London, 2003)
In "Louie & Bloop and the Swapped Shopping," two quirky friends embark on a whimsical adventure when they accidentally mix up their shopping lists. Louie, a curious cat, and Bloop, a playful blob, set out to gather items for each other's unusual lists, leading to hilarious misunderstandings and unexpected discoveries. As they navigate through a colorful marketplace, they learn the value of teamwork and the joy of embracing surprises, ultimately realizing that friendship is the best treasure of all.